Art and the Artist in Society. - Jiménez-Justiniano, José (Cambridge Scholars Publishing, 2013)
Art and Artist in Society is a compilation of essays that examine the nexus between artists, the art they create and society. These essays consider how art has changed its form and role both to accommodate newer trends and to fully participate in society. Divided into six thematic sections, the book examines the works of a diverse group of artists working in a range of art forms, such as writers Milan Kundera and Judith Ortiz Cofer, filmmakers Humberto Solás and Walter Salles, performers/phot ...